2011
DOI: 10.1590/s1516-31802011000600008
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of electrical stimulation on rehabilitation after ligament and meniscal injuries: a systematic review

Abstract: CONTEXT AND OBJECTIVE: Electrical stimulation (ES) is widely used to strengthen muscles following ligament and meniscal injuries. The aim of this study was to evaluate the effectiveness of ES for rehabilitation after soft tissue injuries of the knee treated surgically or conservatively. ; n = 43), seis a oito semanas após cirurgia de reconstrução do ligamento cruzado anterior. CONCLUSÃO: Há evidências de que a ES combinada a exercícios de reabilitação convencional pode ser efetiva na melhora da força muscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…Imoto et al 93 and Kim et al 94 (level A1 systematic reviews) concluded that the addition of electrostimulation to conventional rehabilitation might be more effective in improving quadriceps strength up to 2 months after ACLR. The level A2 RCT of Paternostro-Sluga et al 100 and the level B RCT of Fitzgerald et al 99 were included in both systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Imoto et al 93 and Kim et al 94 (level A1 systematic reviews) concluded that the addition of electrostimulation to conventional rehabilitation might be more effective in improving quadriceps strength up to 2 months after ACLR. The level A2 RCT of Paternostro-Sluga et al 100 and the level B RCT of Fitzgerald et al 99 were included in both systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…However, its effect on long-term functional performance and self-reported knee function is inconclusive 63 93 94 98 101

Level 2 : electromyographic feedback might improve short-term postsurgical pain after ACLR 95 96

…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As principais alterações que irão ocorrer nestes indivíduos serão a diminuição da força e a redução de atividade voluntária muscular, sendo estas mais aparentes na musculatura do quadríceps. Esta lesão pode vir associada a outros mecanismos de lesões mais comuns como de menisco e lesões condrais [18][19][20][21][22] . O tratamento para lesões de LCA, normalmente é cirúrgico, visando restaurar a estabilidade anatômica e funcional da articulação do joelho, sendo que após este procedimento o processo de reabilitação é fundamental tendo como objetivos a serem alcançados a diminuição da dor, controle da inflamação, cicatrização, melhora na amplitude de movimento, prevenção da hipotrofia muscular, ganho de força muscular, manutenção da propriocepção e retorno das atividades de vida diária, existindo assim vários protocolos de reabilitação [23][24][25] .…”
Section: Protocolos De Tratamento Fisioterápico Nas Lesões De Ligamenunclassified